Numerical Investigation of Filtration Influenced by Microscale CO Bubbles in Steel Melt. Issue 2 (26th September 2019) - Asad, Amjad; Aneziris, Christos G.; Schwarze, Rüdiger
Abstract : Herein, the influence of the formation of carbon monoxide bubbles on steel cleaning and inclusion removal is addressed. The focus herein is the effect of filter surface bubbles formation on the level of melt cleanliness and the cleaning efficiency. The CO bubbles develop due to the reaction between carbon and oxygen on the filter's surface. A numerical model is developed to consider the effect of this phenomenon on the cleanliness of steel melt. The CO bubbles leave the filter and capture nonmetallic inclusions, moving them upward in the melt, eventually transporting the inclusions to the free surface of the melt, where they are deposited and removed from the melt. In this model, it is assumed that the bubble volume increases either linearly or exponentially because of this reaction. The results show that the formation of CO bubbles on the filter walls does not significantly increase the number of removed inclusions from the melt compared with the formation of bubbles on the inclusion surface. These results indicate that the formation of CO bubbles on the inclusions surface is the primary cause for the increase of cleanliness of the melt. Abstract : Herein, the influence of the formation of carbon monoxide bubbles on steel cleaning and inclusion removal is dealt with. The results indicate that the formation of CO bubbles on inclusion surface is the primary reason for the increase of cleanliness of the melt.